Covid-19 and mortality among people with diabetes mellitus (Research, Society and Development, 2022)
The study aimed to analyze the mortality of Covid-19 in people with Diabetes Mellitus (DM) in the state of São Paulo. Data were collected in the State Data Analysis System, for the period from February 2020 to July 2021. Comparisons were analyzed using the log-binomial regression model and relative risk calculation. The model comparing patients with and without DM was adjusted for sex, age group, heart disease and obesity, possible confounding variables. Men with DM aged 21 to 30 years had a 74.28% higher risk of death when compared to men without DM. Therefore, it is necessary to monitor changes in age profiles and people considered at high risk to reduce mortality.